Ablation of mitochondrial DNA results in widespread remodeling of the mitochondrial complexome. (20th September 2021) - Guerrero‐Castillo, Sergio; van Strien, Joeri; Brandt, Ulrich; Arnold, Susanne
Abstract: So‐called ρ0 cells lack mitochondrial DNA and are therefore incapable of aerobic ATP synthesis. How cells adapt to survive ablation of oxidative phosphorylation remains poorly understood. Complexome profiling analysis of ρ0 cells covered 1, 002 mitochondrial proteins and revealed changes in abundance and organization of numerous multiprotein complexes including previously not described assemblies. Beyond multiple subassemblies of complexes that would normally contain components encoded by mitochondrial DNA, we observed widespread reorganization of the complexome. This included distinct changes in the expression pattern of adenine nucleotide carrier isoforms, other mitochondrial transporters, and components of the protein import machinery. Remarkably, ablation of mitochondrial DNA hardly affected the complexes organizing cristae junctions indicating that the altered cristae morphology in ρ0 mitochondria predominantly resulted from the loss of complex V dimers required to impose narrow curvatures to the inner membrane. Our data provide a comprehensive resource for in‐depth analysis of remodeling of the mitochondrial complexome in response to respiratory deficiency. Synopsis: Human ρ0 cells devoid of mitochondrial DNA are viable despite being incapable of aerobic ATP synthesis. Complexome profiling analysis of ρ0 mitochondria provides insights how human cells can survive without respiration by reorganizing their mitochondrial proteome. ρ0 cells devoid of mitochondrial DNA exhibit widespread reorganization of the mitochondrial complexome. Covering ∼1, 000 mitochondrial proteins, distinct changes in expression patterns of the protein import machinery, metabolite carriers, and other molecular assemblies were revealed. The comprehensive dataset provides a rich resource to further explore remodeling of the mitochondrial complexome in respiratory deficiency. Abstract : Human ρ0 cells incapable of aerobic ATP synthesis can survive without respiration by reorganizing the mitochondrial proteome.